Ants and crickets: Arbitrary saving rates in an agent-based model with infinitely lived-agents - Gergely Varga; János Vincze (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2015)
Savings behaviour seems to exhibit heterogeneity across nations, and within nations, too. Large changes in saving rates have been observed in the last decades that can be viewed as signs of the arbitrariness of saving. There is a long tradition in the savings literature that separates people into two groups: those who behave soberly (ants), and those who act in an extremely short-sighted fashion (crickets). A puzzle remains: why does an apparently inferior behavioural pattern persist? Our aim is to provide a model that exhibits the arbitrariness of savings by exploring the two-types idea, and also makes intelligible why both types can coexist in the long run. Our approach consists in setting up an agent-based model starting from a traditional production and factor market framework. The model features an evolutionary mechanism that promotes the behaviour conducive to the highest satisfaction of the consumption goal. Our main findings include the prevalence of non-ergodicity, and the genericity of non-stationarity. The model becomes stationary when the selection pressure is very high, and crickets are eliminated. Though in general ants have somewhat higher per capita consumption than crickets, and are less indebted, we have found cases where the total average consumption is higher with many crickets than without them.
Keywords: E03; E14; E27; 330; essential facilities; competition policy; regulation; postal services